Penerapan manajemen strategi di era digital: Tantangan dan peluang - Andiani, Alycia Afina (Maliki Interdisciplinary Journal, 2025)
The digital age has brought significant changes to how organizations manage themselves, including in education and business. Advances in information technology have created a need for strategic management that is both adaptable and innovative, to deal with challenges and take advantage of new opportunities. This article discusses the application of strategic management in the digital era, focusing on key challenges such as technological transformation, human resource gaps, and data security, as well as opportunities that can be seized through digital innovation and cross-sector collaboration. The discussion is based on findings from two related academic journals on strategic management and digital education. Based on the discussion, this article concludes that the success of strategic management in the digital era depends heavily on three main pillars. First, visionary leadership committed to driving digital transformation. Second, continuous investment in human resource competency development to address the digital divide. Third, the development of reliable and secure information technology infrastructure. The implications of this research emphasize the need for a holistic approach that integrates technology, people, and processes to create resilient and competitive organizations amidst digital disruption.